The coral island : a tale of the Pacific Ocean - Ballantyne, R. M. 1825-1894.; Bratton, J. S. (Oxford [England] ; New York : Oxford University Press, 1990)
In this adult edition of the children's classic, three English boys, shipwrecked on a deserted island, create an idyllic society despite typhoons, wild hogs, and hostile visitors. Then evil pirates kidnap one of the youths whose adventures continue among the South Sea Islands.
Includes bibliographical references (p. [xxiii]-xxiv).
Momiul
Keywords: Shipwrecks -- Fiction; Survival -- Fiction; Adventure and adventurers -- Fiction; Islands -- Fiction